Biodiversity and Biogeography of Three Pseudomonas syringae Pathovars which Affect Kiwi Fruit Cultivation - Morán, Félix; Marco-Noales, Ester; Escrich, Ainoa; Barbé, Silvia; López, María M. (Crimson, 2019)
Kiwi fruit is an economically important crop in several countries and it can be affected by several bacterial pathogens. Three pathovars of Pseudomonas syringae have been reported affecting kiwi fruit plants: Pseudomonas syringae pv. actinidiae causal agent of bacterial canker of kiwi fruit; P. syringae pv. actinidifoliorum, causal agent of leaf spot of kiwi fruit, and P. syringae, pv. syringae causal agent of floral buds necrosis. Since there is a high phenotypic and genetic diversity among strains inside these pathovars here are briefly described the main differences found in the kiwi fruit strains of these three pathovars to help in developing preventive and curative control strategies to efficiently manage the bacterial diseases that affect kiwi fruit.